Factores que influyen en la no realización del papanicolaou en mujeres de 15 a 60 años de edad en la parroquia Timbara cantón Zamora. año 2015 - Camacho Torres, Jenny Marivel (2016)
The present study was aimed to determine the factors that influence the performance of all Pap smears of women aged 15 to 60 years in the health post of parish Timbara Zamora Canton in the period January to June 2015. The type of research they used were descriptive, transversal, bibliographic, field, retrospective and prospective. The techniques and instruments were the survey with the questionnaire administered to 103 women. The results were as follows. The prevalence of performing papanicolauo was 16.50%; 27.18% of the women are between 31 and 40 years; marital status are married with 44.66%; ethnicity is mixed with 75.73%, the level of incomplete secondary education with 60.19%, occupation housewife with 84.47%; socioeconomic level is low at 56.31%; the number of children is 2 to 3 with 52.43%; the 88.35% of women have started their active sexual life more than 2 years. The 53.40% its last papanicolauo were between 1 and 3 years; 8.74% received the result of the examinations. Relevant factors for the non-realization of the Pap smear is the neglect of women with 30.10% do not remember when they performed with 17.48; He believes it is not necessary to 16.50%; the 10.68% did not know that the 7.77% had already done for fear that it detected a serious illness; the 6.80% have askance and ashamed of health personnel and 0.97% have no time. an educational proposal based on conferences and home visits were executed; besides promoting and sampling papanicolauo. the percentage of women who have not been performed examining papanicolauo is 16.50% higher conclude, the most important causes neglect. Keywords. Factors influencing, Papanicolauo, women 15 to 60 years